Media Presentation of English Borrowings of Pedagogical Discourse - A. D. Efimova (Дискурс)
Introduction. Currently, the Russian value picture of the world is changing under the influence of American culture as the leader of globalization. Borrowings in different types of discourse become an expression of these changes, the perception of which is formed in media discourse, playing an important role in understanding these borrowings. The purpose of the study is to investigate the features of the media representation of English borrowings of pedagogical discourse.Methodology and sources. The basis of the research was the collected thematic corpus of texts of different genres: texts of forums, articles of media educational platforms and media texts themselves with a total volume of 42 thousand words.Results and discussion. This article examines the features of the media presentation of the key imported concepts of pedagogical discourse “trend” and “rating”, which express the key idea of competitiveness for American culture. The borrowing “trend” is closely related to the contexts of the use of other borrowings included in its content structure: “know-how”, “startup”, “hackathon”, etc. and includes in its interpretative field the concepts of “innovation” and “modernization”, which receive an assessment depending on the subject of the assessment qualification. The interpretative field of the "rating" concept includes words such as “bullying”, “pressure”, “competition”. In most media texts, it is negatively assessed as contributing to a pragmatic approach to gaining knowledge, causing rivalry and negative emotions in children, causing psychological trauma and problems of relationships in the team. The basis for the metaphorical conceptualization of the processes taking place in education is the basic metaphor “man-nature”, as well as the metaphor of computer games and value, which allow us to highlight the value accents of perception and the attitude of society to the phenomena being mastered.Conclusion. It is revealed that the borrowings “trend” and “rating” have figurative and value characteristics, have pronounced evaluative labeling and metaphorical conceptualization. The study of borrowings of pedagogical discourse indicates the importance of the discursive factor in understanding concepts.